2022
DOI: 10.3389/fpsyt.2022.978416
|View full text |Cite
|
Sign up to set email alerts
|

A randomized controlled trial of an mHealth application with nursing interaction to promote quality of life among community-dwelling older adults

Abstract: SignificanceUsing mHealth apps alone at home without the support of healthcare experts could mean that older adults might not fully utilize the functions of the apps, recognize their benefits, and sustain their use. Incorporating an integrated health-social partnership model to support the app usage when further help is needed by the older adults might maximize the apps' benefits in the long term.ObjectivesThis study aimed to examine the benefits of adding nursing interaction supported by a health-social partn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 38 publications
1
7
0
Order By: Relevance
“…In line with our findings, a RCT on 1,372 hypertension patients reported that mobile phone text messages could resulted in a small reduction in SBP compared with usual care after 12 months intervention (6). Also, it was reported that observations, including in-person visits, telephone support, and text messaging may have important implications when conducting internet-based interventions (35,36). So we added mobile devices, including phone calls, short message service, face-to-face communication via video and in-person visits as our intervention methods.…”
Section: Discussionsupporting
confidence: 85%
“…In line with our findings, a RCT on 1,372 hypertension patients reported that mobile phone text messages could resulted in a small reduction in SBP compared with usual care after 12 months intervention (6). Also, it was reported that observations, including in-person visits, telephone support, and text messaging may have important implications when conducting internet-based interventions (35,36). So we added mobile devices, including phone calls, short message service, face-to-face communication via video and in-person visits as our intervention methods.…”
Section: Discussionsupporting
confidence: 85%
“…Participants for this study were community-dwelling older adults who had taken part in an interventional study that sought to examine the effects of mHealth and nurse support [ 23 ]. The participants were recruited from five community and elderly centers that serve more than 50,000 older adults per year.…”
Section: Methodsmentioning
confidence: 99%
“…Following this, another 12-week period was set to ascertain the sustained effects of the combined intervention. The study observed that participants in the mHealth group demonstrated improvement in the Physical Component Summary (PCS) of the Quality-of-Life scale over the 12-week period and sustained to the 12-week follow-up period whereas the mHealth + I group demonstrated improved self-efficacy over the intervention period with a decrease at follow-up [ 23 ]. These beneficial effects notwithstanding, it is interesting to note that the mHealth + I group that received more support experienced minimal improvement which warrants a further study to ascertain how they experienced the use of the mHealth app and the proactive professional support.…”
Section: Introductionmentioning
confidence: 99%
“…New models of care are emerging to improve patient and family outcomes. Now more than ever, patients and community‐dwelling older adults are being empowered to partner with various advanced and low‐end technological applications to self‐manage even in the absence of a healthcare provider (Vaffis et al, 2023; Wong, Bayuo, Wong, Chow, et al, 2023; Wong, Wong, Bayuo, et al, 2022; Wong, Wong, Chow, et al, 2022).…”
Section: Requirement 2: Encompassing All Phenomena Of Interest To The...mentioning
confidence: 99%
“…The metaverse also offers a virtual environment enabled by technology to train nurses (De Gagne et al, 2022). In the communities, nurses continue to employ internet‐based resources and mobile health (mHealth) applications to promote the delivery of person‐centred care across varied population groups such as community‐dwelling older adults (Wong, Bayuo, et al, 2022; Wong, Bayuo, Wong, Chow et al, 2023; Wong, Wong, Bayuo et al, 2022; Wong, Wong, Chow, et al, 2022) and stroke survivors (Burns et al, 2021; Wong, Bayuo, Wong, Kwok, et al, 2023). In fact, as the world battled with the Coronavirus pandemic, these technologies were shown to be the ‘game changers’ in healthcare (Betriana et al, 2022).…”
Section: Introductionmentioning
confidence: 99%